Analysis of YouTube Content about Konjac as an Education of Indonesian Farmers in the Disruption Era - Yunus, Ulani; Rizkiansyah, Mariko; Ariestyani, Arleen; Sukandar, Rudi (LSPR Institute of Communication & Business, 2023)
The konjac plant is thought to be a nutritious meal that is good for both beauty and health. Konjac exports from Indonesia to other countries grew as a result in 2020. Nevertheless, a sharp fall was observed at the end of 2021, despite the fact that many Indonesian farmers had shifted to Konjac plants. The researcher will continue the research series with Konjac plant objects in 2022 because there are so many questions and rumors surrounding this plant. The purpose of this study is to interpret the meaning of YouTube accounts that talk about konjac plants. By generating codes from all the words collected from the 30 YouTube accounts examined, the study employed a qualitative content analysis methodology. Three code frameworks were identified as being relevant to the Konjac problem: Konjac, the Government, and Export. The Government of Indonesia appealed the findings of these three regulations regarding the attitudes of farmers who support and oppose the growing of konjac. The Indonesian government is viewed as being unprepared to deal with both the farmers themselves and the global market, and thus disregards the quality of Konjac crops for export. Conclusion: In order to improve the quality of products that will be exported and brand Konjac plants for the global market, coordination and engagement between farmers and the Indonesian government are required, as well as the involvement of academics.